European relations with Russia threat perceptions, responses, and strategies in the wake of the Ukrainian crisis - Pézard, Stéphanie; Radin, Andrew; Szayna, Thomas S. 1960-; Larrabee, F. Stephen 1944- (RAND Corporation, 2017)
"Russia's illegal annexation and occupation of Crimea in March 2014 has challenged the integrity of Europe's territorial borders and confirmed after the Georgia war in 2008 that Russia could react violently to perceived challenges to what it regards as its sphere of influence. This report first examines how European states perceive Russia's behavior in eastern and northern Europe, and whether they regard Russian policy and behavior in these regions as an important security priority. We identify a number of fault lines within Europe with regard to threat perceptions and further analyze whether these divides extend to perceptions of NATO and the United States. NATO members closer geographically to Russia appear to be most concerned by Russia's aggressive behavior, and are concerned that the Alliance is ill equipped to respond to the current crisis. Second, the report analyzes how European states have responded to Russian behavior. While European states generally agree that a firm response is required, they are also eager to maintain open channels of communication with Russia. Finally, the report examines how European states intend to shape their relationship with Russia in the future; what existing measures they intend to keep in place; what new measures they might implement; and prospects for NATO and EU expansion. This future relationship is based on a general understanding that relations with Russia have changed irremediably; tensions are unlikely to recede anytime soon; and future actions toward Russia will depend on Russian behavior"--Publisher's web site
"Arroyo Center."
Keywords: Außenpolitik; Diplomatische Beziehungen; Internationale Politik; Sicherheitspolitik; Europa; Russland; Ukraine Conflict (2014- ); Ukraine Conflict, 2014-; Europe / Foreign relations / Russia (Federation); Russia (Federation) / Foreign relations / Europe; Diplomatic relations; Europe; Russia (Federation); 2014